An Escrow-Based Peer-to-Peer Online Payment System for Fraud Reduction - Olugbemi Olusanjo Fasola; Ugochukwu Onwudebelu; Achu Edim Etta; Ali Harrison Ugadu (PT. Teknologi Futuristik Indonesia, 2026)
The rapid growth of peer-to-peer (P2P) online commerce has intensified concerns related to trust and fraud, particularly in informal and social-media-driven marketplaces where buyers and sellers often transact without prior relationships. Conventional online payment systems largely rely on trust-based models that inadequately protect participants from fraudulent activities, leading to financial losses and reduced user confidence. This study presents the design and implementation of an escrow-based peer-to-peer online payment system (Escrow-BP2P) aimed at providing an escrow-mediated mechanism intended to reduce fraud risks and enhance transactional trust in P2P transactions. The escrow-BP2P system introduces a trusted third-party escrow mechanism that securely holds buyer payments until transaction conditions are fulfilled and the exchanged goods or services are verified. The system architecture supports buyer, seller, and administrator roles, incorporating payment verification, transaction monitoring, dispute handling, and controlled fund release. Object-Oriented Analysis and Design Methodology (OOADM) is adopted to ensure modularity, maintainability, and system scalability, while the implementation utilizes PHP and MySQL for web-based deployment. The solution is contextualized within the Nigerian e-commerce environment, where online fraud remains a significant challenge. The escrow-BP2P framework demonstrates how structured transaction mediation can improve transactional trust, minimize fraudulent practices, and provide an escrow-based payment management platform for P2P online commerce. The system offers practical insights for deploying trust-enhancing payment infrastructures in emerging digital marketplaces.